2013
DOI: 10.1103/physrevb.88.125305
|View full text |Cite
|
Sign up to set email alerts
|

Group-velocity slowdown in a double quantum dot molecule

Abstract: The slowdown of optical pulses due to quantum-coherence effects is investigated theoretically for an "active material" consisting of InGaAs-based double quantum-dot molecules. These are designed to exhibit a long lived coherence between two electronic levels, which is an essential part of a quantum coherence scheme that makes use of electromagnetically-induced transparency effects to achieve group velocity slowdown. We apply a many-particle approach based on realistic semiconductor parameters that allows us to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 49 publications
0
20
0
1
Order By: Relevance
“…Thus, for the same inversion N , the gain on the intersubband transition is larger than that on an interband transition in the QD. The choice of the polarization dephasing of γ d = 1.0 meV is motivated by the restrictions that it has to be higher than intersubband dephasing for the case of unpopulated QD scattering states and a small carrier density in the QWs ( γ d < 0.1 meV), 50 but lower than an interband dephasing with an appreciable population in the QD scattering states ( γ d up to 10 meV). 56 We will plot the small signal gain in addition to the inversion between the optically active states in the following.…”
Section: A Inversion (Gain) For Fixed Qw Carrier-densitiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, for the same inversion N , the gain on the intersubband transition is larger than that on an interband transition in the QD. The choice of the polarization dephasing of γ d = 1.0 meV is motivated by the restrictions that it has to be higher than intersubband dephasing for the case of unpopulated QD scattering states and a small carrier density in the QWs ( γ d < 0.1 meV), 50 but lower than an interband dephasing with an appreciable population in the QD scattering states ( γ d up to 10 meV). 56 We will plot the small signal gain in addition to the inversion between the optically active states in the following.…”
Section: A Inversion (Gain) For Fixed Qw Carrier-densitiesmentioning
confidence: 99%
“…Thus, we follow Ref. 50 and introduce an effective quasi-particle broadening for the scattering contributions. By using an effective quasi-particle broadening we work with polarons, i.e., quasi-particles that include the effect of the coupling to phonons, instead of the "naked" QD electronic levels.…”
Section: 49mentioning
confidence: 99%
See 2 more Smart Citations
“…Also they have found that coulomb interactions shift the molecular resonance of charged exciton with respect to the single charge, enabling the QDs lightinduced coupling. Theoretically, Michael et al [9] explored the slowdown of optical pulses due to the quantum coherence effects for an active material consisting of double InGaAs-based QD molecules. Also the dependencies of slowdown, the shape of propagating probe pulses on lattice temperature and drive intensities have been explored as well.…”
Section: Introductionmentioning
confidence: 99%